Uso de emojis y la comunicación digital en WhatsApp por los estudiantes de la Facultad de Ciencias de la Salud y del Ser Humano – UEB, en el período académico septiembre – diciembre 2024 - Lanas Narváez, Pamela Lizeth (2025)
The general objective of the project analyzes the influence of the use of emojis in digital communication among students of the Faculty of Health Sciences and the Human Being in the academic period September - December 2024. The work was born from the idea to defend that the use of emoticons allows expressing emotions, contexts and meanings, but they do not replace written language in the interaction between university students through instant messaging. The methodology employed is descriptive with a mixed approach, collecting data on the use of conversational visual symbols and their impact on messages between students. The main results showed that a large majority of students use these visual paralinguistic elements to complement a message, mainly to clarify the emotional tone of the message, and also when they implement them in chats with teachers they feel a closer communication and therefore accessible. The findings indicate that students use these symbols as a meaningful complement to their digital communications, allowing them to carry emotional nuances that text alone does not convey.